"Whispers Heard at the Pictures": women's work in early cinema. Issue 4 (2nd October 2021) - Drummer, Emily; Sanders, Lise Shapiro
ABSTRACT: In this essay, we offer a comparative analysis of women service workers in early cinema in Britain and the United States from the 1910s to the 1930s. Although this period has been the subject of much important scholarship in film history over the past several decades, women's experiences as box office attendants, cashiers, cigarette girls, purveyors of ice cream and sweets, and especially as usherettes, constitute an under-researched field. Tracing the narratives surrounding women's work in a wide variety of capacities in early cinema auditoriums can illuminate much about how women were perceived as employees and sexualized as objects of the gaze of male patrons, while, at the same time, acting as spectators and mediators with a privileged perspective on both the screen and the audience. In pursuing this line of inquiry, we draw not only on existing scholarship, but also on our own original research on industry journals, girls' and women's popular magazines, star and fan culture, and changing conditions for women's labor and leisure in the interwar period.